Mitrou Archaeological Project (University, 2003)
[Dt.:] MAP (Mitrou Archaeological Project) ist ein Projekt, das sich mit der Erforschung und Ausgrabung der bronzezeitlichen Siedlung Mitrou, welche in der östlichen Lokris in Griechenland lag, beschäftigt. Auf der Website gibt es Informationen zum Projekt, zur Siedlung, Bilder der Funde und des Areals des Surveys und Informationen zur im Sommer 2008 startenden Grabungskampagne. - [Engl.:] MAP (Mitrou Archaeological Project) is a project which is devoted to research and excavation of the Bronze Age settlement Mitrou. It is located in East Lokris, Greece. On the web site there is information about the project and the settlement, there are pictures of the findings and the environment where the survey takes place.